2018
DOI: 10.11152/mu-1655
|View full text |Cite
|
Sign up to set email alerts
|

Elastography in prostate gland imaging and prostate cancer detection

Abstract: Transrectal prostate biopsies under ultrasonography guidance remain the gold standard for the detection of prostate cancer (PCa). Transrectal ultrasonography (TRUS), however, has a limited sensitivity in PCa detection. Prostate elastography (TRES) increases the sensitivity of a TRUS examination. Therefore, the aim of this review is to discuss the usefulness of TRES in prostate gland imaging for the diagnosis and management of prostate cancer based on published literature. The advantages of transrectal elastogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…What's more, strain elastography was more operator dependent and less reproducible in comparison with SWE. At present, SWE is broadly applied in various apparatus [10][11][12][13][14] with great feedback. However, there has been limited research in the usability of SWE in peripheral pulmonary lesions [15].…”
Section: Introductionmentioning
confidence: 99%
“…What's more, strain elastography was more operator dependent and less reproducible in comparison with SWE. At present, SWE is broadly applied in various apparatus [10][11][12][13][14] with great feedback. However, there has been limited research in the usability of SWE in peripheral pulmonary lesions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the diagnostic performance of elastography for prostate cancer. In 2018, Tyloch et al reported a review of six meta-analyses that evaluated the use of elastography in the diagnosis of prostate cancer 17 . According to this study, the meta-analysis by Sang et al showed that the highest diagnostic performance, sensitivity, and speci city were 0.844 (range, 0.696-0.927) and 0.860 (range, 0.792-0.908) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that ultrasound (US) elastography can improve the accuracy of PCa diagnosis (24)(25)(26)(27)(28)(29), by evaluating the stiffness of the lesion (30) and guiding the targeted biopsy (29,31). To date, a prediction model that combines lesion elasticity with MP-MRI and clinical data in men with PSA grey zone levels has not been reported.…”
Section: Introductionmentioning
confidence: 99%